Cervical cancer screening preference among Inuit women in Nunavik, Quebec - Gabrielle Gosselin; Patricia Blais; Noémie Smith; Paul Brassard (International Journal of Circumpolar Health)
Self-sampling for oncogenic human papillomavirus (HPV) offers an alternative to the Papanicolaou (Pap) test for cervical cancer screening. We aimed to assess Inuit women’s cervical cancer screening preferences. Eligible Inuit women aged between 25 and 65 in 2022–2023 were given the choice between self-sampling, sampling performed solely by the nurse or the Pap test and were administered a questionnaire on screening preference. Thematic analysis was performed on qualitative data collected through a questionnaire asking if and why women prefer HPV self-sampling or the Pap test for cervical cancer screening. A total of 103 women agreed to participate. Of these, 12 (11.6%) chose to have the nurse perform the HPV test rather than self-collect. Among the 91 left for analysis, 80.2% (73) of women who self-sampled preferred self-sampling to the Pap test and 82.4% (75) would prefer self-sampling in the future. The most common reason given was comfortability (54.9%) and privacy (25.2%). Participants that did not prefer self-sampling (n = 7) expressed desire for a physical exam by the nurse or a lack of confidence in their ability to collect the sample. Eleven either did not indicate a preference, were unsure, or indifferent to cervical cancer screening method. This represents an improvement from a previously conducted study in 2012 among the same population who reported a preference for HPV self-sampling of 56%.